The Role of Firm Characteristics in Enhancing The Dividend Payout Ratio - Halim, Kusuma Indawati (Universitas Pendidikan Nasional, 2023)
The research explores the influence of Corporate Social Responsibility (CSR), leverage, and managerial ownership on the dividend payout ratio in Manufacturing Companies listed on the Indonesia Stock Exchange between 2017 and 2021. This study, based on purposive sampling of 12 companies, employs multiple linear regression to analyze the relationship between these factors and dividend policy. The aim is to uncover how CSR practices, leverage strategies, and managerial ownership impact dividend decisions. The findings indicate a positive association between Corporate Social Responsibility initiatives and leverage with the dividend policy. Conversely, managerial ownership exhibits a negative effect on the dividend payout ratio. These results suggest that companies emphasizing CSR activities and utilizing leverage strategies tend to favor higher dividend payouts. Conversely, higher managerial ownership seems to lead to reduced dividend payouts. These insights shed light on the intricate dynamics between corporate behavior, financial structures, and managerial influences in shaping dividend policies within the Indonesian manufacturing sector.